2020
DOI: 10.1073/pnas.2020205118
|View full text |Cite
|
Sign up to set email alerts
|

Affinity of small-molecule solutes to hydrophobic, hydrophilic, and chemically patterned interfaces in aqueous solution

Abstract: Performance of membranes for water purification is highly influenced by the interactions of solvated species with membrane surfaces, including surface adsorption of solutes upon fouling. Current efforts toward fouling-resistant membranes often pursue surface hydrophilization, frequently motivated by macroscopic measures of hydrophilicity, because hydrophobicity is thought to increase solute–surface affinity. While this heuristic has driven diverse membrane functionalization strategies, here we build on advance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(57 citation statements)
references
References 103 publications
4
47
0
Order By: Relevance
“…Note that there is a similar but slightly different approach to decompose the Gibbs energy into the three parts. 11,102 In this type of method, MD simulations of purely repulsive solute molecules are required in addition to the MD simulations of the nonpolar solute molecules.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that there is a similar but slightly different approach to decompose the Gibbs energy into the three parts. 11,102 In this type of method, MD simulations of purely repulsive solute molecules are required in addition to the MD simulations of the nonpolar solute molecules.…”
Section: Methodsmentioning
confidence: 99%
“…[4][5][6][7][8][9] Organic molecules, including proteins, often bind strongly to hydrophobic surfaces. [10][11][12] Brushes of hydrophilic polymers exhibit fouling resistance when the coverage is high enough on the hydrophobic surface. [13][14][15][16][17][18] This antifouling property has attracted great interest in many fields such as medical implants, biosensors, marine equipment, water purification, and desalination.…”
Section: Introductionmentioning
confidence: 99%
“…Such detailed insights require a dissection of the free energy into meaningful contributions, which include a multitude of enthalpic and entropic terms associated with intramolecular and intermolecular interactions and the corresponding degrees of freedom. Experimental and computational advances improve our ability to isolate individual free energy components, which can provide critical insights into the microscopic driving forces of protein conformational flexibility, , ligand binding, and the interface association of ions and molecules. …”
Section: Introductionmentioning
confidence: 99%
“…When a small non-polar solute binds a hydrophobic surface, water can no longer hydrogen bond around the solute; binding is thus accompanied by the release of constrained hydration waters, and ought to be favored by entropy (Figure 4e) [17]. However, the thermodynamic signatures of such processes can be sensitive to the binding context [38,124]. For example, Setny et al [125] found that the binding of methane to a concave pocket was favored by enthalpy, rather than entropy.…”
Section: B Binding Of Small Solutes To Large Solutesmentioning
confidence: 99%